Transvaginal mesh, gender and the ethics of clinical innovation. Issue 5 (19th May 2020) - Wiersma, Miriam; Kerridge, Ian; Lipworth, Wendy
Abstract: On 10 October 2018, Australian Health Minister Greg Hunt issued a national apology to the Australian women who experienced 'horrific outcomes' following surgery using transvaginal mesh—acknowledging the 'historic agony and pain that has come from mesh implantation'. This apology followed many decades of 'innovative' use of transvaginal mesh for the treatment of pelvic organ prolapse. We use the case of transvaginal mesh to explore how clinical innovation may not only harm patients, but also entrench vulnerability and exacerbate existing inequities—in this case, those relating to gender.